Acute bilirubin encephalopathy in term neonates: a hospital-based study - Iqbal, Javaid; Sharma, Sunil Dutt; Jamwal, Ashu; Saini, Ghanshyam (International Journal of Research in Medical Sciences, 2019)
Background: Acute Bilirubin Encephalopathy and kernicterus is an important cause of cerebral palsy, developmental delay and hearing impairment in low-middle income countries. Interventions such as universal screening for neonatal jaundice, Rhesus immunoglobulins, intensive phototherapy and exchange transfusion have made kernicterus rare in high income countries, but in our set up such cases continue to be reported. Methods: Retrospective observational study where case records of term neonates brought to the neonatal ICU with signs and symptoms of acute bilirubin encephalopathy during the years 2016 and 2017 were sought and analysed. Results: A total of ten term babies reported to the neonatal unit with severe hyperbilirubinemia along with signs and symptoms of bilirubin encephalopathy of which 60% were females. 90% had a birth weight of more than 2.5 kg and mean birth weight was 2.7±0.25 kgs. All the babies were out born. A 4 babies were born at home of which 3 pregnancies were completely unsupervised during the antenatal period. 90% of the babies were from the rural areas, 6 of the cases were from the districts Rajouri, Poonch and Reasi where the terrain is hilly, 2 from rural areas of Jammu and 1 from Kathua. Only 1 was from the Jammu city. The age at admission ranged from 3-9 days and serum bilirubin from 24 to 43.3 mg %. A 5 babies had ABO incompatibility, 1 Rh incompatibility, 1 sepsis, while no cause could be found in 3. Conclusions: Neonatal jaundice is often not easily appreciated by mothers and caregivers in the home setting until it becomes severe enough, at which point neurological damage may have already occurred. There is an urgent need to train the primary health care personnel in assessment and early identification of risk factors for severe neonatal hyperbilirubinemia. They can help the families to seek prompt treatment for this preventable cause of cerebral palsy and mental retardation.